Moses and Abraham Maimonides : encountering the Divine - Lobel, Diana (Emunot., 2021)
"Moses Maimonides-a proud heir to the Andalusian tradition of Aristotelian philosophy-crafted a bold and original philosophical interpretation of Torah and Judaism. His son Abraham Maimonides is a fascinating maverick whose Torah commentary mediates between the philosophical interpretations of his father, the contextual approach of Biblical exegetes such as Saadya, and the Sufi-flavored illuminative mysticism of his Egyptian Pietist circle. This pioneering study explores the intersecting approaches of Moses and Abraham Maimonides to the spark of divine illumination and revelation of the divine name Ehyeh asher Ehyeh, "I am that I am / I will be who I will be.""--